Pelaksanaan Kebiasaan Ghasab Santri Putri Melalui Pelaksanaan Pendidikan Akhlak Di Pondok Pesantren - naning siti fatimah; Jauhan Budiwan; Nur Anas (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2023)
This research aims to determine the causes of the ghasab habits of female students at the Roudlotul Huda Islamic Boarding School, Kedungpanji Lembeyan, Magetan, the implementation of moral education for female students at the Roudlotul Huda Islamic Boarding School, Kedungpanji Lembeyan, Magetan, and the implications of moral education for the decline in the ghasab habits of female students at the Roudlotul Huda Islamic Boarding School, Kedungpanji Lembeyan. Magetan. This research is field research with a qualitative approach. Data was taken through interviews, observation and documentation. The data collected regarding the causes of delusional habits, the implementation of moral education and the impact of moral education, were analyzed using the Miles and Hubberman interactive modeling technique. The research results show that the causes of female students' ghasab habits are based on individual factors and circumstances. The implementation of moral education at the Roudlotul Huda Islamic boarding school is through Islamic boarding school education. The implications of moral education for decreasing female students' ghasab habits at the Roudlotul Huda Islamic boarding school are quite effective in reducing female students' ghasab habits and have an impact on the formation of female students' morals.